Assertiveness Training of Novice Psychiatric Nurses: A Necessary Approach - Laranjeiro, Carlos António (2020)
The statement “assertiveness is both a skill and a choice” is a popular expression in nursing. Being assertive is a core communication skill, which can be learned like many other skills. Appropriate communication skills are critical for novice psychiatric nurses, helping them develop competency for acute care and recovery. The notion of assertiveness has been extensively used in the nursing literature and has been established as a key approach for avoiding adverse occurrences in health care, boosting patient safety (Omura, Levett-Jones & Stone, 2019). Lazarus (1973, cited in Pipas & Jaradat, 2010) identified specific classes of assertive responses, namely the ability to deny a client’s requests, to make requests of the client, to express positive and negative feelings, and to initiate and hold a conversation.